Effect of preventive chemotherapy with praziquantel on schistosomiasis among school-aged children in sub-Saharan Africa: a spatiotemporal modelling study. Issue 1 (January 2022) - Kokaliaris, Christos; Garba, Amadou; Matuska, Martin; Bronzan, Rachel N; Colley, Daniel G; Dorkenoo, Ameyo M; Ekpo, Uwem F; Fleming, Fiona M; French, Michael D; Kabore, Achille; Mbonigaba, Jean B; Midzi, Nicholas; et al.
Summary: Background: Over the past 20 years, schistosomiasis control has been scaled up. Preventive chemotherapy with praziquantel is the main intervention. We aimed to assess the effect of preventive chemotherapy on schistosomiasis prevalence in sub-Saharan Africa, comparing 2000–10 with 2011–14 and 2015–19. Methods: In this spatiotemporal modelling study, we analysed survey data from school-aged children (aged 5–14 years) in 44 countries across sub-Saharan Africa. The data were extracted from the Global Neglected Tropical Diseases database and augmented by 2018 and 2019 survey data obtained from disease control programmes. Bayesian geostatistical models were fitted to Schistosoma haematobium and Schistosoma mansoni survey data. The models included data on climatic predictors obtained from satellites and other open-source environmental databases and socioeconomic predictors obtained from various household surveys. Temporal changes in Schistosoma species prevalence were estimated by a categorical variable with values corresponding to the three time periods (2000–10, 2011–14, and 2015–19) during which preventive chemotherapy interventions were scaled up. Findings: We identified 781 references with relevant geolocated schistosomiasis survey data for 2000–19. There were 19 166 unique survey locations for S haematobium and 23 861 for S mansoni, of which 77% (14 757 locations for S haematobium and 18 372 locations for S mansoni ) corresponded to 2011–19. Schistosomiasis prevalence among school-aged children in sub-Saharan Africa decreased from 23·0% (95% Bayesian credible interval 22·1–24·1) in 2000–10 to 9·6% (9·1–10·2) in 2015–19, an overall reduction of 58·3%. The reduction of S haematobium was 67·9% (64·6–71·1) and that of S mansoni 53·6% (45·2–58·3) when comparing 2000–10 with 2015–19. Interpretation: Our model-based estimates suggest that schistosomiasis prevalence in sub-Saharan Africa has decreased considerably, most likely explained by the scale-up of preventive chemotherapy. There is a need to consolidate gains in the control of schistosomiasis by means of preventive chemotherapy, coupled with other interventions to interrupt disease transmission. Funding: European Research Council and WHO.